Simulation study on liquid droplet size measurement inside venturi scrubber - Nur Tantiyani Ali Othman; Simreth Kaur Dhalywala (Penerbit Universiti Kebangsaan Malaysia, 2020)
Droplet distribution is an importance factor to observe scrubber’s performance as uniform droplets distribution improved the particle’s collection efficiency at minimal liquid usage. Yet, the optimization problem typically involves complicated model functions to predict particle’s collection efficiency and pressure drop. Since the interaction between liquid droplets and gas phase is complex and difficult to solve by an experimental approach. Thus in this study, the prediction of liquid droplet’s behavior in the venturi scrubber was observed by using computational fluid dynamic. The liquid was injected through two orifices on the throat wall. The droplet size at different position was observed at various range of a gas velocity from 70 to 100 m/s and the ratio of liquid to gas of 0.07 to 2.0 L/m3 to determine the optimum absorption rate. The droplet’s breakup in the venturi scrubber was observed using ANSYS© simulation where two-fluid model Eulerian-Eulerian approach was applied. It shows as the gas passes through the throat section, the velocity increases gradually and as it passes through the divergent section, it decreases causing the droplet diameter to increase. Typically, the gas velocity in the throat section is between 30-120 m/s, however in this simulation, the gas velocity of 70-105 m/s shown an adequate to achieve the optimum absorption rate. Besides, the liquid to gas ratio less than 0.06 was insufficient to cover the throat, and by increasing it up to 1.0 does not significantly improve the particle collection efficiency as the velocity at the scrubber’s throat drops which a larger droplets diameter was formed.